Autistic Spectrum Disorders and Creativity: Comparative Study of the Art Works - Aleksandrovich, Maria; Zoglowek, Herbert (Revija za elementarno izobraževanje, 2014)
The purpose of this paper is to outline the findings of a pilot study, which compares drawings of typically developed preschool children and children with autistic spectrum disorders in the same age. In the study the Goodenough-Harris Drawing Test (GHDT) (1926; 1963) was used. In this study, the auto-portraits of children from two groups were analyzed concerning such categories as line, size, colour, details. For this the statistical analysis of variance was used. The results of the study show that there are no statistically significant differences in the drawings of studied groups according to the categories line, size, colour, details.
Keywords: drawings; creativity; TD children; ASD children; auto-portrait